Summary of Elders' interviews -- Support from Anthropological sources - Hickey, Lynne (Canadian Plains Research Centre, 1974)
14 p. transcript of a summary of interviews with various Elders, compiled by Lynne Hickey in May 1974. Tape number IH-341A, transcript disc 31. Ms. Hickey uses various anthropological and historical sources to throw some light on the way in which the Indians of the Treaty 6 and 7 regions might have interpreted the treaty promises. Other no